Bioreactor Design for Sustainable Energy: Case Study of Cow Manure Waste - Baharrudin, Rafief; Ardiansah, Nur (Proceeding International Conference on Religion, Science and Education, 2025)
The potential of cow manure in Indonesia presents an opportunity to be utilized in technological development, particularly using livestock waste as raw material. This technological development aims to produce alternative fuel to replace LPG for cooking purposes. The processing of cow manure into biogas offers significant economic benefits. Furthermore, the use of cow manure as a raw material for biogas can reduce dependence on fossil energy sources and provide a sustainable and efficient energy solution for national energy needs. The development of bioreactor technology also has the potential to increase energy efficiency in communities, support the productivity of mushroom cultivation, and contribute to better waste management through the prudent use of cow manure. Biogas, as one of the processed products, is a combustible natural gas, with the main components being methane (CH4), hydrogen (H2), and carbon dioxide (CO2). This composition makes biogas an attractive alternative energy source for further development. However, most biodigester installations for biogas production remain relatively simple, necessitating the development of better system designs to support effective biogas production monitoring. In this study, the biodigester installation is designed with dimensions of 14.326 meters in length, 4.991 meters in width, and 1.992 meters in depth. The objective of this research is to design a biodigester apparatus capable of processing cow manure waste into renewable energy, such as biogas, which can be utilized by local communities for cooking and mushroom cultivation. In addition to biogas, another by-product is liquid waste from the biogas processing, which can be used as liquid fertilizer, while solid waste can be utilized as planting media for the surrounding community.